4x-9+17=3x+5

Simple and best practice solution for 4x-9+17=3x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-9+17=3x+5 equation:


Simplifying
4x + -9 + 17 = 3x + 5

Reorder the terms:
-9 + 17 + 4x = 3x + 5

Combine like terms: -9 + 17 = 8
8 + 4x = 3x + 5

Reorder the terms:
8 + 4x = 5 + 3x

Solving
8 + 4x = 5 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
8 + 4x + -3x = 5 + 3x + -3x

Combine like terms: 4x + -3x = 1x
8 + 1x = 5 + 3x + -3x

Combine like terms: 3x + -3x = 0
8 + 1x = 5 + 0
8 + 1x = 5

Add '-8' to each side of the equation.
8 + -8 + 1x = 5 + -8

Combine like terms: 8 + -8 = 0
0 + 1x = 5 + -8
1x = 5 + -8

Combine like terms: 5 + -8 = -3
1x = -3

Divide each side by '1'.
x = -3

Simplifying
x = -3

See similar equations:

| w=5m-10 | | 4(2)(2)= | | -4(6x-3)= | | 6=2/3x-6 | | 6x+25=16-3x | | 27-10x=7 | | (X-4)(x+9)=(x+5)(x-3) | | 12x+7=15x-14 | | 3x=288x | | N-7=3+2n | | 2x+1=5x-44 | | f(x)=(6+4x+3x^2)*(2+4x+2x^2) | | -5=3x-29/4 | | 5v^2+44v+32=0 | | 4(-1+4)=12 | | y=6(3)-39 | | x-3=-5x-9 | | (2k+3)(5k+1)= | | 9+5w-1w=12-6w | | 10m^2-53m+36=0 | | 7x+2x-3x=3(x-8) | | y=2(3)-25 | | .01(900-30x)=9.8x+400 | | 3x^2=288x^2 | | 9+5w-14x=12-6w | | y=3(3)-22 | | 5(2x+6)=4(-5-2x)3x | | x-4=-4x-2 | | 4m-19-11=70 | | 6r-18=30 | | 18=-3y-12 | | 87-x=136 |

Equations solver categories